2012
DOI: 10.1007/s10552-012-9902-4
|View full text |Cite
|
Sign up to set email alerts
|

Perceived effectiveness of pictorial health warnings among Mexican youth and adults: a population-level intervention with potential to reduce tobacco-related inequities

Abstract: Purpose Pictorial health warnings on cigarette packages are a prominent and effective means of communicating the risks of smoking; however, there is little research on effective types of message content and socio-demographic effects. This study tested message themes and content of pictorial warnings in Mexico. Methods Face-to-face surveys were conducted with 544 adult smokers and 528 youth in Mexico City. Participants were randomized to view 5–7 warnings for two of 15 different health effects. Warnings for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
156
5
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 142 publications
(179 citation statements)
references
References 21 publications
12
156
5
6
Order By: Relevance
“…8 A 20-minute computer assisted, interviewer-administered faceto-face survey was conducted using laptop computers. Recruitment sites included two large public parks, a bus terminal, and outside five Walmart stores in Mexico City.…”
Section: Sample and Recruitmentmentioning
confidence: 99%
See 3 more Smart Citations
“…8 A 20-minute computer assisted, interviewer-administered faceto-face survey was conducted using laptop computers. Recruitment sites included two large public parks, a bus terminal, and outside five Walmart stores in Mexico City.…”
Section: Sample and Recruitmentmentioning
confidence: 99%
“…8 Each set of HWLs that addressed the same health effect included 5 to 7 warnings, with various themes. Images were drawn by authors from actual HWL implemented in several countries and adapted where necessary.…”
Section: Hwl Health Effect and Themementioning
confidence: 99%
See 2 more Smart Citations
“…Thus, in an era of mobile devices in all parts of the world, radio remains influential. The two related studies from Mexico found that graphic pictorial health warnings that included diseased organs or tobacco victims had a greater impact on participants than symbolic representations or testimonials [19,20]. Furthermore, these effects may be magnified among persons from less advantaged SEP.…”
mentioning
confidence: 99%